Bank complexity and core competence of commercial banks in Vietnam: The buffer role of corporate social responsibility - Hung Quang Phung; Khoa Dang Duong; Phuc Huu Truong; Anh Quynh Pham; Hoa Thanh Phan Le (PLoS ONE, 2025)
Based on stakeholder theory, socially responsible practices may help firms gain competitive advantages by lowering operational costs and enhancing their core competencies. From the perspective of the conglomerate hypothesis, we further suggest that CSR can act as a mechanism to reduce hidden risks, as firms, particularly banks, tend to diversify their activities more extensively. Using a sample of 26 commercial banks in Vietnam from 2010 to 2023, we test a set of hypotheses and find that engaging in CSR and diversifying operations are associated with lower risk exposure, greater financial stability, and improved asset quality. Moreover, the positive effects are more evident in large banks. In contrast, smaller banks may incur relatively higher costs when combining CSR efforts with operational complexity, potentially offsetting the benefits. Our study underscores the role of CSR as a foundation for income diversification and core competence enhancement, offering practical implications for policymakers in emerging countries to foster sustainable development in the banking sector.